Strategic IT transformation at Accenture - Jeffery, Mark ([London] : SAGE, 2016)
In 2001 Accenture took the bold step of separating from its parent, Arthur Andersen. The new firm that emerged had a bright future ahead, but it also faced the challenge of building a new IT infrastructure that could support a global organization that consults on leading-edge technology. Accenture's CIO at the time, Ed Schreck, knew that becoming a master of your own trade was not an easy task. Frank Modruson, Schreck's successor and the person responsible for carrying forward the IT transformation challenge from 2002 on, had ambitious plans for the new technology infrastructure that was to replace Arthur Andersen's legacy systems. Difficult decisions had to be made. This case study examines this topic.
Originally Published in: Jeffery, M., Fisher, D., Granot, M., Kadyan, A., Pho, A. & Vasquez, C. (2010). Strategic IT Transformation at Accenture. 5-110-002. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Accenture (Firm); Information technology -- Management -- Case studies